Adaptation of Neisseria gonorrhoeae to the Female Reproductive Tract. (August 2020) - Song, Wenxia; Yu, Qian; Wang, Liang-Chun; Stein, Daniel C
Gonorrhea, caused by Neisseria gonorrhoeae, is a common sexually transmitted infection and an urgent public health problem. Humans are the exclusive host, and the genital tract with heterogeneous epithelia is the primary niche of this bacterium, creating unique challenges for understanding its pathogenesis. The cervical tissue explant model that we have developed enabled us to show that the properties of the epithelial cells in the female reproductive tract are the main factors driving gonococcal adaptation. Gonococcal variants that colonize strongly and penetrate poorly, thereby causing asymptomatic infection, survive better in the cervix. Gonococci adapt to different epithelial cell types by varying their surfaces and modulating distinct epithelial cell-cell adhesion complexes through manipulation of host cell signaling. These findings provide critical new insights on the mechanisms by which N. gonorrhoeae adapts to the human mucosal surface and causes asymptomatic infection.